Association between the change in body mass index from early adulthood to midlife and subsequent type 2 diabetes mellitus. Issue 3 (2nd February 2016) - Sun, Wanwan; Shi, Lixin; Ye, Zhen; Mu, Yiming; Liu, Chao; Zhao, Jiajun; Chen, Lulu; Li, Qiang; Yang, Tao; Yan, Li; Wan, Qin; Wu, Shengli; et al.
Abstract : Objective: To clarify the quantitative relationship of body mass index (BMI) change from early adulthood to midlife with presence of type 2 diabetes mellitus (T2DM) after midlife. Methods: This study included 120, 666 middle‐aged and elderly, whose retrospectively self‐reported body weight at 20 and 40 years and measured height were available. BMI at 20 and 40 years and BMI change in between were defined as early‐adulthood BMI, midlife BMI, and early‐adulthood BMI change. Results: The odds ratio (OR) for T2DM associated with an 1‐unit increment of early‐adulthood or midlife BMI was 1.08 (95% confidence interval (CI), 1.07‐1.08) and 1.09 (95% CI, 1.09‐1.10) respectively. In the cross‐tabulation of both early‐adulthood BMI and BMI change, the prevalence of T2DM increased across both variables. Compared with participants with normal early‐adulthood weight and BMI increase/decrease ≤1, the OR (95% CI) for T2DM of participants with early‐adulthood overweight/obesity and BMI increase ≥4 kg/m 2 was 3.49 (3.05‐4.00). For participants with early‐adulthood underweight and BMI increase/decrease ≤ 1, the OR (95% CI) was 0.85 (0.75‐0.97). Subgroup analysis according to sex and age showed similar trends. Conclusions: Early‐adulthood BMI may influence T2DM prevalence after midlife independent of current BMI. T2DM prevalence after midlife was positively associated with early‐adulthood weight gain and inversely related to early‐adulthood weight loss, while early‐adulthood weight loss could not completely negate the adverse effect of early‐adulthood overweight/obesity on diabetes.